Hybridization of sugar-carboxylate-syngas platforms for the production of bio-alcohols from lignocellulosic biomass (LCB) – A state-of-the-art review and recommendations. (15th November 2019) - Chowdhury, Ranjana; Ghosh, Shiladitya; Manna, Dinabandhu; Das, Sumona; Dutta, Sambit; Kleinsteuber, Sabine; Sträuber, Heike; Kamrul Hassan, Md.; Kuittinen, Suvi; Pappinen, Ari
Graphical abstract: Highlights: Sugar, carboxylate and syngas platforms are the major routes for bioalcohol production. Hybridization among the three platforms enhances sustainability of bioalcohols from LCB. Merits and demerits of the current hybrids of SP, CP and SyP are assessed and discussed. CONVER-B is an advanced hybrid model of three platforms for LCB-to-bioalcohol generation. Abstract: Lignocellulosic biomass (LCB), the most abundant renewable feedstock for bioenergy generation, is commonly converted to second generation bioalcohols, the main drop-in fuels for petroleum gasoline, through three technologies based on sugar, carboxylic acid and syngas platforms. The hybridization of either any two or three platforms altogether is a novel concept aimed at improvement of yield and quality (high heating value) of bioalcohols. This article reviews the present status of the integration techniques of hybrid platforms with an overall assessment of their advancement with respect to their individual counterpart as well as the challenges involved. It has been indicated that to extract the maximum benefit of hybridization, research studies should be spurred in the fields of kinetic analysis of all thermochemical and biochemical processes, microbial interaction, optimization of process parameters (pH, temperature), performance analysis of engine for the utilization of mixed product bioalcohols, sustainability analysis through the development of mathematical models for lab-scale operations and process simulation models for large scale units along with life cycle assessment. Moreover, pyrolysis of LCB has been identified as a unique central process for the supply of all intermediate compounds, namely, sugar, carboxylic acid and syngas during the hybrid networking of three platform technologies. In this context, the scheme of CONVER-B, a joint research project under the INNO-INDIGO partnership program, aiming at sustainable integration of the platforms to produce bio-alcohols from LCBs leaving zero effluent simultaneously with carbon sequestration potential has been introduced and discussed.